1994
DOI: 10.1146/annurev.pu.15.050194.000245
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Statistical Data in the Biomedical and Health Sciences: Ethical, Institutional, Legal, and Professional Dimensions

Abstract: data as public good INTRODUCTION A 1992 report issued from the National Research Council observes: "The general norms of science emphasize the principle of openness. Scientists are generally expected to exchange research data as well as unique research materials that are essential to the replication or extension of reported findings." (34). While these norms have been acknowledged over centuries, the actual practice of sharing research data has varied widely even within individual disciplines , and until recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Reasons for encouraging data sharing in the social sciences are many (Fienberg, 1994;King, 1995). Data sharing increases the transparency of quantitative analytic work, thereby lending more credibility to research findings, providing evidence to support analytic frameworks and decisions, and a source for researchers to consult when considering how to build upon existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for encouraging data sharing in the social sciences are many (Fienberg, 1994;King, 1995). Data sharing increases the transparency of quantitative analytic work, thereby lending more credibility to research findings, providing evidence to support analytic frameworks and decisions, and a source for researchers to consult when considering how to build upon existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Open data is said to ensure accountability in research by allowing others access to researchers’ data and methods [1-4]. Having research data available to peers and the public helps to ensure that reported study results are valid and protects against faulty data [1-8].…”
Section: Introductionmentioning
confidence: 99%
“…The available of open health data for secondary use is fundamental for advance in the medical knowledge. The use of public datasets by researchers has effects on the acceleration of scientific advances as well as improvements in both the efficiency and efficacy of health processes [36]. A responsible use of individual's data must be guaranteed, but it is possible to reconcile individual data privacy with socially valuable uses [37].…”
Section: Challenges and Risksmentioning
confidence: 99%